2019
DOI: 10.1002/cap.10058
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Amalgam Tattoo With a New Technique: Mucoabrasion and Free Connective Tissue Graft

Abstract: Introduction A new technique was performed for the removal of an amalgam tattoo (AT), consisting in mucoabrasion combined with a free connective tissue graft (FCTG). Case Presentation A 59‐year‐old female presented with a large AT involving the alveolar mucosa and gingiva between teeth #7 and #8, where endodontic treatment and apicoectomy was performed 21 years ago. To avoid compromising esthetics, the lesion was managed with a new technique including mucoabrasion and an FCTG. At the 53‐month follow‐up, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The novel modality EL-MIKS is different from the previously reported procedure combined with periodontal plastic surgery [7][8][9][10]. It is much less invasive, results in less intraoperative and postoperative pain, and has a short treatment time followed by fast and favorable wound healing, as well as excellent esthetic improvement.…”
Section: Difference From Conventional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel modality EL-MIKS is different from the previously reported procedure combined with periodontal plastic surgery [7][8][9][10]. It is much less invasive, results in less intraoperative and postoperative pain, and has a short treatment time followed by fast and favorable wound healing, as well as excellent esthetic improvement.…”
Section: Difference From Conventional Methodsmentioning
confidence: 99%
“…However, few studies have been conducted on the removal of metal tattoos. Furthermore, while studies on periodontal plastic surgery have reported methods, such as the use of free gingival grafts [7] and connective tissue grafts [8][9][10] to remove metal tattoos, optimal treatments have not been well studied or established.…”
Section: Introductionmentioning
confidence: 99%
“…Despite awareness about this phenomenon for many years, 10 treatment methods are yet to be established, because of difficulties associated with treatment procedures and the lack of suitable instruments. Previous case studies' findings have shown that surgical treatments to remove pigmented gingiva, namely, connective tissue grafts (CTGs) 11‐13 and free gingival grafts (FGGs), 14 are invasive, complicated, and not always effective at removing tattoos, and these procedures are associated with risks, including postsurgical gingival recession and defects.…”
Section: Introductionmentioning
confidence: 99%
“…Two techniques to address this problem will be discussed: Masking of the tattoo with a keratinized gingival graft (KGG), 16 and removal following treatment with a connective tissue graft (CTG). [17][18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“…Usually these pigmentations are only a concern for the patient when the tattoo is in their smile zone. Two techniques to address this problem will be discussed: Masking of the tattoo with a keratinized gingival graft (KGG), 16 and removal following treatment with a connective tissue graft (CTG) 17‐20 …”
Section: Introductionmentioning
confidence: 99%